Src Inhibition Attenuates Neuroinflammation and Protects Dopaminergic Neurons in Parkinson’s Disease Models - Yang, Hanyu; Wang, Lu; Zang, Caixia; Wang, Yue; Shang, Junmei; Zhang, Zihong; Liu, Hui; Bao, Xiuqi; Wang, Xiaoliang; Zhang, Dan (Frontiers in Neuroscience, 2020)
Chronic neuroinflammation is of great importance in the pathogenesis of Parkinson’s disease (PD). During the process of neuroinflammation, over-activated microglia release many pro-inflammatory factors, which eventually induce neurodegeneration. Inhibition of excessive microglial activation is regarded as a promising strategy for PD treatment. Src is a non-receptor tyrosine kinase which is closely related to tumors. Recently, some reports indicated that Src is a central mediator in multiple signaling pathways including neuroinflammation. The aim of our study was to demonstrate the role of Src in microglial regulation and neuroinflammation. The lipopolysaccharide (LPS) -stimulated BV-2 microglia model and the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) -induced PD model were applied in this study. The results showed that inhibition of Src could significantly relieve microgliosis and decrease levels of inflammatory factors. Besides, inhibition of Src function reduced the loss of dopaminergic neurons and improved the motor behavior of the MPTP-treated mice. Thus, this study not only verified the critical role of Src tyrosine kinase in neuroinflammation, but also further proved that interfering neuroinflammation is beneficial for PD treatment. More importantly, this study shed a light on the hypothesis that Src tyrosine kinase might be a potential therapeutic target for PD and other neuroinflammation-related diseases.